Sweeteners from the Panela Agroindustry: natural and nutritious products - Recalde Luna, Sandra; Zambrano Bosquez, Juan; Cuzco Cruz, María; Quiñonez Bustos, Jenny; Quezada Torres, Walter; Quezada Moreno, Walter; Suarez Castro, Edder (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
The quality, safety and performance of various food products are influenced by the development of good agricultural and manufacturing practices, which applies to sweeteners from the panela agro-industry. The objective of the work was to evaluate the weaknesses that reduce the sector as the effect of quality in the process, especially due to clarification, performance in the production of hydrolyzed honey, panela and natural sugar, and subjective quality through color as a measure. of acceptance and rejection. Methodologically, the weaknesses of the sector were identified, highlighting technological, market, economic, environmental, agricultural and management aspects. A process diagram was produced as a work procedure to establish improvements in the production stages through experimental studies. It is concluded that, applying intensification criteria in the purification of the juice by using natural clarifiers, diversifying, and producing hydrolyzed honey, greater productivity is achieved due to its yield. In addition, the color as a measure of acceptance or rejection of the sweetener obtained, where manufactures are induced for purposes of nutritional quality, safety, competitiveness, and sustainability of the sector.